2019
DOI: 10.1101/523142
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comparative analysis of ionic strength tolerance between freshwater and marine Caulobacterales adhesins

Abstract: 17Bacterial adhesion is affected by environmental factors, such as ionic strength, pH, 18 temperature, and shear forces, and therefore marine bacteria must have developed holdfasts 19 with different composition and structures than their freshwater counterparts to adapt to their 20 natural environment. The dimorphic a-proteobacterium Hirschia baltica is a marine budding 21 bacterium in the Caulobacterales clade. H. baltica uses a polar adhesin, the holdfast, located at 22 the cell pole opposite the reproductive… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
54
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(54 citation statements)
references
References 69 publications
(140 reference statements)
0
54
0
Order By: Relevance
“…26,27 In C. crescentus, deacetylation of holdfast polysaccharides is important for both the cohesiveness and adhesiveness of holdfast. 27 In our previous work comparing H. baltica and C. crescentus holdfasts, 25 we showed that both species use similar genes to synthesize, export, and anchor holdfast to the cell envelope. We identified H. baltica genes that modify holdfast in C. crescentus, namely the putative acetyltransferase hfsK (hbal_0069) and the polysaccharide deacetylase hfsH (hbal_1965; Fig.…”
Section: The Holdfast Polysaccharide Deacetylase Hfsh Is Required For Adhesion and Biofilm Formation In H Balticamentioning
confidence: 83%
See 3 more Smart Citations
“…26,27 In C. crescentus, deacetylation of holdfast polysaccharides is important for both the cohesiveness and adhesiveness of holdfast. 27 In our previous work comparing H. baltica and C. crescentus holdfasts, 25 we showed that both species use similar genes to synthesize, export, and anchor holdfast to the cell envelope. We identified H. baltica genes that modify holdfast in C. crescentus, namely the putative acetyltransferase hfsK (hbal_0069) and the polysaccharide deacetylase hfsH (hbal_1965; Fig.…”
Section: The Holdfast Polysaccharide Deacetylase Hfsh Is Required For Adhesion and Biofilm Formation In H Balticamentioning
confidence: 83%
“…As holdfast is required for biofilm formation in C. crescentus and H. baltica, 20,25,31 we probed for the presence of holdfasts using fluorescent Alexa Fluor 488 (AF488) conjugated wheat germ agglutinin (WGA) lectin that specifically binds to the GlcNAc component of the holdfast polysaccharide. 20 In exponentially growing planktonic cultures, C. crescentus WT cells produced holdfasts that bound AF488-WGA and formed cell-cell aggregates mediated by holdfasts, called rosettes (Fig.…”
Section: The Holdfast Polysaccharide Deacetylase Hfsh Is Required For Adhesion and Biofilm Formation In H Balticamentioning
confidence: 99%
See 2 more Smart Citations
“…Hentchel et al (2019) grew axenic cultures of C. crescentus in complex and chemically defined media to examine the fitness of transposon mutants in freshwater environments and described a new model system to study gene function in ecosystems. In a comparison of the physicochemical properties of adherence between freshwater and marine Caulobacterales , Chepkwony, Berne, and Brun (2019) found the marine Hirschia baltica maximized binding via their holdfast in environments with high ionic strength. Caulobacter crescentus shifts cell morphology in response to changing growth conditions (Heinrich, Leslie, Morlock, Bertilsson, & Jonas, 2019).…”
Section: Bacteriamentioning
confidence: 99%